Movimientos sociales, nueva razón de estado y la estigmatización de la protesta social en Colombia (2015)
The purpose of this paper is to explain the social and political dynamics involved the exercise of freedom of assembly in a democratic State. Under an explanatory perspective, a number of scenarios in which the links between social movements, neoliberalism and the criminalization of social protest are established showing how the political dynamics supported in the deterritorialization of the economy, the privatization of social and political guarantees as well as the tightening of legal policies that reduce social freedoms, blur the collective purposes of social movements in Colombia